KARAKTERISTIK EDIBEL FILM DARI PATI AREN AMILOSA TINGGI DAN APLIKASINYA SEBAGAI PENGEMAS BUBUK BUMBU MIE - Abdul Rahim; Nur Alam; Haryadi Haryadi; Umar Santoso (Universitas Tadulako, 2011)
The purpose of this study was to determine the characteristics of edible films made from highamylase arenga starch, and its application as noodle seasoning powder packing. The treatment wasfractionated natural arenga starch at 70 and 80oC. Edible film was constructed from arenga starchsolution at a concentration of 2.8% (w/v) added with glycerol plus solution 0.5% (w / v) and thenheated at 85oC for 5 minutes. The next process was the addition of palm oil (palmitic acid) with aconcentration of 10% (w / w polymer) in the same condition. The solution then was poured in aplastic plate and oven dried at 50oC for 18-24 hours. Once dried, it was cooled at room temperaturefor 15 minutes. Parameters observed at this stage were thickness, water vapor transmission rate,tensile strength and elongation. The results showed that characteristics of edible films producedfrom the arenga starch at 70oC included thickness 0.103 mm, water vapor transmission rate(WVTR) 5.09 g/m2h, tensile strength 32.76 MPa and elongation 2.60%; while for the fractionatedarenga starch at 80oC included thickness 0.104 mm, the WVTR 2.55 g/ m2h, tensile strength 44.03MPa and elongation 1.71%. It is suggested that edible films produced from fractionation can beapplied as packing noodle seasoning powder that dissolves less than 3 minutes.